Communication in Emergency Situations - Hlavnova, Anna; Hlavna, Vladimir (Communications - Scientific letters of the University of Zilina, 2002)
Communication in emergency situations requires not only specific verbal but also non-verbal competencies of persons involved. Verbal communication comprises, apart from speech culture and the way language is used, also language competence which is to be properly applied in discourse. If language competence fails, non-verbal communication (body language) takes place.